2011
DOI: 10.1002/mnfr.201000525
|View full text |Cite
|
Sign up to set email alerts
|

Antiglycative and neuroprotective activity of colon‐derived polyphenol catabolites

Abstract: Some polyphenolic catabolites, generated in vivo in the colon, were able in vitro to counteract two key features of diabetic complications, i.e. protein glycation and neurodegeneration. These observations could lead to a better control of these events, which are usually correlated with hyperglycemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
145
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 174 publications
(150 citation statements)
references
References 54 publications
4
145
0
1
Order By: Relevance
“…Some polyphenols may inhibit the later stages of glycation by preventing the binding of dicarbonyls to protein amino groups. 30 Verzelloni et al 31 suggest that phenolic compounds may inhibit the formation of Amadori products because of their specific binding to albumin. However, the effect of pomegranate juice on glycation appears to be independent of its binding to albumin; a similar pattern of inhibition is also observed in proteins that do not extensively bind phenolics (gelatin and immunoglobulin G, data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Some polyphenols may inhibit the later stages of glycation by preventing the binding of dicarbonyls to protein amino groups. 30 Verzelloni et al 31 suggest that phenolic compounds may inhibit the formation of Amadori products because of their specific binding to albumin. However, the effect of pomegranate juice on glycation appears to be independent of its binding to albumin; a similar pattern of inhibition is also observed in proteins that do not extensively bind phenolics (gelatin and immunoglobulin G, data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Proposed pathways for the conversion of punicalagin to ellagic acid and urolithins in anaerobic fecal suspensions. (Verzelloni et al, 2011), and phenolic catabolites are also reported to have anti-inflammatory effects (Larrosa et al, 2009). FIG.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence linking intake of ellagitannins to health benefits. This finding is based principally on research with pomegranate juice, which contains ellagitannins in the form of punicalins and punicalagin (Aviram et al, 2000;Pantuck et al, 2006;Rosenblat et al, 2006;Belal et al, 2009;Larrosa et al, 2010;Verzelloni et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…(2) An increase in the antioxidant capacity of caecal content and in the expression of endogenous antioxidant Table 2. Summary of biological effects described for polyphenol metabolites Metabolites Biological effect Reference (2 )-Epicatechin conjugates Effects on flow-mediated vasodilation in human subjects (72) 3-Phenylpropionic acid, 3-hydroxyphenylacetic acid, 3-hydroxyphenylpropionic acid COX-2 inhibition in HT-29 intestinal cells (73) 3,4-Dihydroxyphenylacetic acid, hydroferulic acid Anti-inflammatory activity in CDD-18 colon fibroblast cells (74) Hydrocaffeic acid Reduction of oxidative stress in DSS-treated rats (74) Urolithin A, urolithin B, dihydroferulic acid Protein glycation inhibition (75) Urolithin A, urolithin B Antiproliferative effects through change in the expression levels of growth factor receptors, oncogenes and tumour suppressors in Caco-2 intestinal cells (76) COX-2, cyclo-oxygenase-2; DSS, dextran sodium sulfate. systems, thus counteracting the tumour-promoting reactive oxygen species (ROS) present in the colon (84,85,89,90) .…”
Section: Gastrointestinal Healthmentioning
confidence: 99%